Workshop time management system - Abd. Samad, Hasan Basari (2005)
The Workshop Time Management System is a web-based application that is specially built for the third party logistics provider and workshops, with the goals to improve efficiency and shortening processing time by automating all processes and workflows involved in a central application. This project will focus more on human resources planning and efficiency such as pending job assignment, mechanic job log, task efficiency, evaluation of mechanic performance and mechanic duty shift control. By implementing the new solutions to the system, the maintenance staff will be better informed of pending jobs or faults at the workshop whereas the mechanics will be able to access the necessary information instantly to rectify the problem. A number of improvements on the existing features will also be included, such as urgent task handling, vehicle quality inspection and job activation to ensure more accurate time estimation and further improve the flexibility of the system in handling the various situations. The project will be carried out systematically with the waterfall model of Software Development Life Cycle and Structured System Analysis and Design Methodology. The business process and environment is analyzed to enable a more thorough understanding of the problems, opportunities and directives that triggered the project. Overall, this project is expected to deliver a range of mission-critical applications, including a proprietary environmental compliance database for its corporate administrative staff, and a fleet management application for its vehicle maintenance crew at the workshop.